2018
DOI: 10.11591/ijeecs.v10.i3.pp1257-1265
|View full text |Cite
|
Sign up to set email alerts
|

A Review in E-Government Service Quality Measurement

Abstract: <span lang="EN-US">Governments are responsible for providing services to the public easily, efficiently, therefore they introduced electronic government as a way to minimize costs, enhance services, save time and augment performance and efficacy in the public sector. E-service Quality is one of the critical issues in the failure or success of e-government projects. It promotes the efficiency and effectiveness of governments and the relationships with users and enhances their satisfactions. Measurement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
(49 reference statements)
0
9
0
1
Order By: Relevance
“…-Achieving the efficiency of the electronic service provided -Achieve efficiency in engineering internal governance structures and processes -Equal provision of service, organizational structures, and human resources to suit the application and implementation of information and communication technologies (Isaac, 2007;Kaur et al, 2020;Kraay, 2018 2020), the United Nations presented a report containing an index to measure e-government, and it was completed Registering it as a quantitative indicator for the report, and then developing it into a theoretical model that combines the elements of e-government, e-readiness, and e-participation, in addition to e-government practices, and this composite index measures the capacity of governments from three main aspects and represents its sub-indicators as follows: E-Service Measurement Index: the scope and quality of service provision benefit evaluation and provision, and the level of -Availability (Al-Nidawi et al, 2018;Kraay, 2018;Un, 2016;Verma et al, 2005); Communications infrastructure index: the extent to which the foundations of information and communication technology are being exploited. Calculate primary factors including readiness and utilization (Das et al, 2017;Kraay, 2018;Nawafleh et al, 2012;Un, 2016); Human Capital Index: reflects available skills, educational levels, and the government's ability to spread -knowledge (Al-dweeri et al, 2019;KASSEN & Scholar, n.d.;Kim, 2018;Kraay, 2018;Porumbescu, 2016) The report explains the imperative of the three aforementioned indicators that measuring e-government is considered an evaluation The country's use of the Internet to provide information, products, and services, as well as the level of wired communications And wireless and infrastructure development, and human capital in every country, and through these aspects, the measurement may reach reliability in its results.…”
Section: Methods For Measuring and Evaluating Egovernment Performance Proposed By International Organizationsmentioning
confidence: 99%
“…-Achieving the efficiency of the electronic service provided -Achieve efficiency in engineering internal governance structures and processes -Equal provision of service, organizational structures, and human resources to suit the application and implementation of information and communication technologies (Isaac, 2007;Kaur et al, 2020;Kraay, 2018 2020), the United Nations presented a report containing an index to measure e-government, and it was completed Registering it as a quantitative indicator for the report, and then developing it into a theoretical model that combines the elements of e-government, e-readiness, and e-participation, in addition to e-government practices, and this composite index measures the capacity of governments from three main aspects and represents its sub-indicators as follows: E-Service Measurement Index: the scope and quality of service provision benefit evaluation and provision, and the level of -Availability (Al-Nidawi et al, 2018;Kraay, 2018;Un, 2016;Verma et al, 2005); Communications infrastructure index: the extent to which the foundations of information and communication technology are being exploited. Calculate primary factors including readiness and utilization (Das et al, 2017;Kraay, 2018;Nawafleh et al, 2012;Un, 2016); Human Capital Index: reflects available skills, educational levels, and the government's ability to spread -knowledge (Al-dweeri et al, 2019;KASSEN & Scholar, n.d.;Kim, 2018;Kraay, 2018;Porumbescu, 2016) The report explains the imperative of the three aforementioned indicators that measuring e-government is considered an evaluation The country's use of the Internet to provide information, products, and services, as well as the level of wired communications And wireless and infrastructure development, and human capital in every country, and through these aspects, the measurement may reach reliability in its results.…”
Section: Methods For Measuring and Evaluating Egovernment Performance Proposed By International Organizationsmentioning
confidence: 99%
“…The model was divided into five dimensions: Tangibles, Reliability, Responsiveness, Assurance and empathy. However, according to [32] (cited in [26])it was argued that the SERVQUAL model could be applied to the Internet, though there is a necessity to modify its dimensions to be more applicable to technology, making it more technologically relevant and not as dependent on personal interactions. [26]Conducted an intense study on the service quality model and proposed 10 dimensions to assess the quality of egovernment services, which was based on the dimensions proposed by different researchers in the literature.…”
Section: Table 1:e-government Service Quality Definitionmentioning
confidence: 99%
“…E-GOVERNMENT SYSTEM QUALITY DIMENSION 5.1 Service Quality Definition One definition of service quality is the difference and comparison between a customer's expectation of a service and the customer's perception of the service provided [24], [25], [26]. However, evaluating and assessing the service quality has been repeated in the literature [24], [25], [27] due to difficulty in measuring tangible components.…”
mentioning
confidence: 99%
“…The main components to be examined are the people in the organization, the technology, and the organization itself. Therefore, the employees' technical skills, awareness and attitude, infrastructure, cultural change and technological readiness are the readiness index components to be evaluated [9]. The framework indicated in Table 1 and Figure 1 shows the readiness cutpoints [10].…”
Section: E-health Readiness Assessment Frameworkmentioning
confidence: 99%
“…System quality, information quality, and service quality are the technological factors that influence the adoption of information [12]. The qualities of the technology itself, the quality of the information provided by the technology and the service that the technology renders affect user satisfaction and are crucial factors for successful adoption [9,16]. A study conducted in Indonesia also confirmed that these three technological factors are decisive determinants of e-health acceptance and use [17].…”
Section: The Technology Factormentioning
confidence: 99%